DIAJUKAN SEBAGAI TUGAS PENGEMBANGAN KEPROFESIANBERKELANJUTAN (PKB) SESUAI PERATURAN MENPAN RBNO: 16TAHUN 2009 - Safinah Azmir Safinah (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
Mathematics is one of the important subjects in realizing a meaningful mathematics learning process. Mathematics learning that is integrated in real life and can provide moral values to students. Teachers must be creative and innovative in choosing strategies, methods and approaches that are appropriate to pandemic conditions. Distance learning emergencies. Learning activities are designed in such a way as to provide learning experiences that involve the mental and physical processes of students. The learning process is through interaction between students and teachers, teachers with parents and the environment at a distance. Strategies, methods and approaches are work steps that must be prepared in order to achieve basic competencies. The learning experience in question can be realized through the use of a variety of student-centered learning strategies.